Racism and classism in the film Emancipation (2022): A socio-political analysis - Khansa Dzaky Nurkharitsna; Yusrina Dinar Prihatika (Universitas Pakuan, 2025)
Slavery was an integral part of the history of the founding of the United States. This phenomenon gave rise to views of racism and classism that disregarded the essence and dignity of human beings who were not considered human. This study aims to uncover the practices of racism and classism depicted in the film Emancipation (2022). This article employs a descriptive qualitative method with a behavioral approach within a socio-political framework. Data collection techniques were conducted by watching and analyzing the film Emancipation (2022). The data obtained consisted of facts, descriptions, and information about the issues depicted in the film Emancipation (2022). The results of this study indicate that racism and classism during the era of slavery were complex phenomena that were interrelated. The physical violence and dehumanization depicted in the film align with the definition of slavery, which emphasizes the use of power and violence to maintain control and exploitation.